2017
DOI: 10.21595/jve.2017.18381
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low frequency 2-10 Hz vibrations on blood circulation in lower extremities

Abstract: This pilot study gives evidence on the effect of low frequency 2-10 Hz vibration on young physically inactive subjects and associations with blood flow in limbs. For the study purposes, low frequency 2-10 Hz vibration was applied for the subjects in the lying position, and a special device, patented at Kaunas University of Technology, was used to generate low frequency vibrations. Altered temperatures in feet were measured with a thermovisual camera, which records thermal changes. Thermovisual measurement was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Vessel vasodilation and subsequent increases in the SBF induced by vibration are mainly regulated via two mechanisms: (i) the pulsating mechanical forces act on the endothelial cells to release NO and NO synthase (NOS), which contributes to vessel vasodilation; (ii) Simulation of polymodal receptors on the skin surface by the vibration could cause the release of neuropeptides, and further induce nerve axon reflex-related microvascular vasodilation (Sackner et al, 2005; Napoli et al, 2006; Nakagami et al, 2007). The study of Gailiuniene et al showed that low frequency 2–10 Hz vibration could not make any significant changes in foot temperature and blood flow (Gailiuniene et al, 2017). While high frequency vibration was reported to be harmful to vascular, musculoskeletal, and nervous system function (Govindaraju et al, 2010; Gailiuniene et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vessel vasodilation and subsequent increases in the SBF induced by vibration are mainly regulated via two mechanisms: (i) the pulsating mechanical forces act on the endothelial cells to release NO and NO synthase (NOS), which contributes to vessel vasodilation; (ii) Simulation of polymodal receptors on the skin surface by the vibration could cause the release of neuropeptides, and further induce nerve axon reflex-related microvascular vasodilation (Sackner et al, 2005; Napoli et al, 2006; Nakagami et al, 2007). The study of Gailiuniene et al showed that low frequency 2–10 Hz vibration could not make any significant changes in foot temperature and blood flow (Gailiuniene et al, 2017). While high frequency vibration was reported to be harmful to vascular, musculoskeletal, and nervous system function (Govindaraju et al, 2010; Gailiuniene et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The study of Gailiuniene et al showed that low frequency 2–10 Hz vibration could not make any significant changes in foot temperature and blood flow (Gailiuniene et al, 2017). While high frequency vibration was reported to be harmful to vascular, musculoskeletal, and nervous system function (Govindaraju et al, 2010; Gailiuniene et al, 2017). According to the previous studies, vibration interventions with frequencies range from 20 to 50 Hz were beneficial to improving blood microcirculation, and 50 Hz vibration may achieve a higher increase of skin blood flow (Lohman et al, 2007, 2011; Nakagami et al, 2007; Maloney-Hinds et al, 2008; Lythgo et al, 2009; Merriman and Jackson, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature and vibration control can be used to maintain the erythrocytes quality during transportation. The vibration frequency in blood storage boxes or cooler boxes during transportation must be maintained at not exceeding 10 Hz for 10 minutes because a vibration frequency that is large enough can cause damage to the cell membranes of erythrocytes and platelets [10]. Hence, we need a tool that can stabilize vibrations with a frequency of ≤ 10 Hz to maintain the safety and quality of blood.…”
Section: Introductionmentioning
confidence: 99%